Bipolar coagulation - capable microforceps. - Kawai, T. (IEEE Engineering in medicine and biology magazine)
Microforceps that can be used with the hyper utility mechatronic assistant system (HUMAN) for bipolar coagulation in minimally invasive neurosurgery were developed. A method of using two sets of those forceps for bipolar coagulation was developed, in which electrical current is passed through the drive wires to the forceps tips to form an electrical circuit. A prototype mechanism that employs a torque tube to achieve an opening and closing speed of 138°/s was fabricated. A forceps drive system that has a delay time of 0.06 s was constructed by using a fast control algorithm. In vivo experiments on rat abdomen and rat brain blood vessels confirmed that the bipolar coagulation function is of a practical level. Three neurosurgical clinicians confirmed the good operability and practicality of the gripping function in experiments on a human cadaveric brain. Furthermore, both doctors and engineers confirmed that the microforceps described here can be used in their present form in tumor removal and other such procedures. Following these basic engineering experiments, basic medical experiments (including experiments on the optimum distance between the lens of the endoscope and, the object of manipulation), various surgical procedures performed on living rat brain, surgical simulations performed on a human cadaver, and experiments on safety in ethylene oxide gas sterilization were performed. They lead to the conclusion that clinical use of the HUMAN system is feasible.